Podcast—The Remediation of Radio: A Media Theoretical Framework for Podcast Research - Mónika Andok (Journalism and Media)
The study aims to investigate, describe, and contextualize the media theoretical characteristics of podcasts. Initially, it examines the media technological advancements that facilitated the emergence of podcasts, followed by an exploration of the parallel innovations in content production. Subsequently, the analysis focuses on key dimensions relevant to defining podcasts as a medium: the evolution of audio technology, the heterogeneity of content, and the patterns of individual and collective usage. The transition of podcasts from a novel cultural form to a recognized medium was a gradual process spanning approximately two decades. The aim of this study is to examine how podcasts emerged as a distinct medium, combining the characteristics of traditional radio with modern digital technologies, using Bolter and Grusin’s remediation concept as a media theoretical framework. This paper posits that the most suitable theoretical framework for understanding podcasts as a medium is Bolter and Grusin’s theory of remediation. According to this framework, media are defined through processes of remediation. In the case of podcasts, however, a unique form of convergent remediation emerges, wherein the medium integrates elements of traditional radio with the distinctive characteristics of networked communication.